A novel interleukin 36 gamma for diagnosing and differentiating malignant from infectious pleural effusion - Nashwa A. Amin; Asmaa E. Mohamed; , Shimaa M.E. Wahdan; Amira E. Ramadan; Shimaa M. Mohammed; Marwa S.E. Abd-Elraouf; Kout A.M. Diab (Egyptian Journal of Chest Disease and Tuberculosis)
Background Pleural effusions can be caused by various diseases, making their diagnosis challenging. Light’s criteria are often used to distinguish transudative and exudative effusions. Exudative effusions have a more complex etiology, including parapneumonic, tuberculous, and malignant effusion. Objectives The main objective of this study was to evaluate the effectiveness and sensitivity of Interleukin 36 gamma (IL-36γ) as a diagnostic marker for differentiating between malignant and infectious pleural effusions. Methods The study involved 100 patients with pleural effusion. Patients were categorized into five groups based on their final diagnosis. An ELISA technique was used to quantitatively measure the levels of pleural fluid IL-36γ. Results The results showed that pleural IL-36γ levels were higher in tuberculous pleural effusion compared with malignant, transudative, and uncomplicated pleural effusion. In contrast, pleural IL-36γ levels were higher in complicated pleural effusion compared with tuberculous, malignant, transudative, and uncomplicated pleural effusion. Conclusion Based on the study’s findings, it was concluded that pleural IL-36γ is a novel biomarker that can be used to diagnose and differentiate malignant pleural effusion from infectious pleural effusion.